2018
DOI: 10.15766/mep_2374-8265.10738
|View full text |Cite
|
Sign up to set email alerts
|

A Project-Based, Resident-Led Quality Improvement Curriculum Within a Pediatric Continuity Clinic

Abstract: IntroductionParticipation in quality improvement (QI) projects is required of pediatric residents, and evidence-based medicine has highlighted the importance of providing residents with experiential practice in this realm. Embedding QI projects within a continuity clinic provides residents an opportunity for meaningful involvement in QI efforts.MethodsA QI curriculum was implemented within a pediatric residency program that included an introductory lecture on QI principles and participation in resident-led, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The model of trainee-led QI programmes are relatively sparse in the literature. There have been successful trainee-led programmes aimed at improving patient satisfaction (37), increasing compliance with venous thromboembolism prophylaxis (38), reducing opioid analgesia discharge prescriptions (39) and other programmes (40,41). This study demonstrates that within a structured programme, surgical trainees can deliver improvement at a national level.…”
Section: Discussionmentioning
confidence: 75%
“…The model of trainee-led QI programmes are relatively sparse in the literature. There have been successful trainee-led programmes aimed at improving patient satisfaction (37), increasing compliance with venous thromboembolism prophylaxis (38), reducing opioid analgesia discharge prescriptions (39) and other programmes (40,41). This study demonstrates that within a structured programme, surgical trainees can deliver improvement at a national level.…”
Section: Discussionmentioning
confidence: 75%
“…Kiger and Bertagnoli outlined their resident quality improvement curriculum and found that residents perceived this curriculum positively, improved their fund of knowledge in quality improvement work and completed 4 projects in their first 2 years following the implementation of this curriculum in 2015. 19 Multiple studies looking at orthopedic, neurosurgery, and vascular surgery residents have demonstrated success in quality improvement initiatives and education. [20][21][22] Residents overall felt that there was significant value added to their education and future careers by taking part in quality improvement projects.…”
Section: Discussionmentioning
confidence: 99%
“…It focuses on core PBLI and SBP competencies while engaging residents in quality improvement initiatives that foster better patient care. While there are QI curricula published (Keefer et al, 2016;Stewart et al, 2016;Wener, 2017;Vinas et al, 2018;Kiger and Bertagnoli, 2018), this resource represents the first QI curriculum specific to PM&R residents.…”
Section: Introductionmentioning
confidence: 99%